An association between MEFV mutation and ANCA-associated vasculitis involving the central nervous system and lungs: causality under scrutiny - Marcus Villander Barros de Oliveira Sá; Amanda Brito; Miriam Baié; Flávio Pacheco; Luydson Vasconcelos (European Journal of Case Reports in Internal Medicine)
Familial Mediterranean fever (FMF) is traditionally associated with biallelic mutations in the MEFV gene; however, heterozygous mutations may also contribute to disease phenotypes. We report the case of a 42-year-old woman with heterozygous p.Met694Ile MEFV mutation, presenting with antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis involving the central nervous system and lungs. Her clinical course was marked by immune dysregulation, autoimmunity and inflammatory manifestations, including urticarial neutrophilic dermatoses and IgM deficiency. This case highlights the potential pathogenic role of heterozygous MEFV mutations in ANCA-associated vasculitis, expanding the clinical spectrum of FMF-related inflammatory diseases. Genetic investigation is essential in patients with overlapping autoimmune and autoinflammatory features to guide appropriate diagnosis and management.